First trimester expression of anorectal malformation: Case report and review of the literature. Issue 9 (19th September 2018) - Liberty, Gad; Bardin, Ron; Gilboa, Yinon; Tover, Ana; Mashiach, Reuven; Mazaki, Eyal; Shen, Ori
Abstract: A 26‐years‐old woman, underwent an ultrasound examination at 13.4 weeks. A cystic structure was identified in the right lower abdomen. Gradually, the cystic mass was replaced by echogenic content and eventually attained the appearance of hyperechoic bowel. At 21.2 weeks, the anal sphincter could not be demonstrated which was consistent with the diagnosis of isolated anal agenesis. Amniocentesis revealed 46XY karyotype with normal comparative genomic hybridization. After termination of pregnancy at 23 weeks, an autopsy revealed an isolated high type anorectal malformation (ARM) without fistula. We reviewed all 14 cases reported in the literature of first trimester sonographic expression of ARM.